Overview of Postpartum Depression in The Sungai Durian Public Health Center Area - Senia Angi Giyandari; Sinaga, Jojor Putrini; Mistika Zakiah; Fitri Sukmawati; Alex (Faculty of Medicine, Universitas Airlangga, 2025)
Introductions: Postpartum depression is a mood disorder that occurs after childbirth, with symptoms lasting more than six months. The prevalence rate of postpartum depression globally is 17.22%. The cases of postpartum depression in Asia are quite high, ranging from 9.29% to 60.93%. The frequency of this disorder in Indonesia is between 11% and 30%. Postpartum depressive disorder can affect the health of the mother, child, and husband. This influence can cause behavioral and emotional problems and even death. This study was conducted to determine the description of postpartum depression in the Sungai Durian Health Center area. Methods: This study was descriptive, with a cross-sectional approach followed by 104 research respondents. Respondents completed an informed consent sheet, personal identity, and the Edinburgh Postnatal Depression Scale (EPDS) Questionnaire. The data was analyzed using the univariate analysis method in Microsoft Excel 2019. Results: This study shows that postpartum mothers who do not tend to experience symptoms of postpartum depression (EPDS score <10) amounted to 66.35%, and postpartum mothers with a tendency to experience symptoms of postpartum depression (EPDS score ≥10) amounted to 33.65%. The results showed that mothers who tended to experience symptoms of postpartum depression were mostly in the age range of 20-35 years, had a high school education, had a family income less than 2,600,000/regency minimum wage, were housewives, were married, were multiparous, had a vaginal delivery, and were getting social support. Conclusion: Postpartum mothers in the Sungai Durian Health Center area do not tend to experience symptoms of postpartum depression.